Exercise and the immune system - Pedersen, B. (1999)
In essence, the immune system is enhanced during moderate and severe exercise, and only intense long-duration exercise is followed by impairment of the immune system. The latter includes suppressed concentration of lymphocytes, suppressed natural killer cell activity, lymphocyte proliferation and secretory IgA in saliva. During the time of immune impairment, referred to as "the open window", microbial agents, especially viruses may invade the host and infections may be established. One reason for the "overtraining effect" seen in elite athletes could be that this window of opportunism for pathogens is longer and the degree of immunosuppression more pronounced. Alterations in metabolism and metabolic factors may contribute to exercise-associated changes in immune function. Reductions in plasma-glutamine concentrations, altered plasma-glucose level, free oxygen radicals and prostaglandins (PG) released by the elevated number of neutrophils and monocytes may influence the function of lymphocytes and contribute to the impaired function of the later cells. Thus, nutritional supplementation with glutamine, carbohydrate, anti-oxidants or PG-inhibitors may, in principle, influence exercise-associated immune function. Although several intervention studies have been performed, it is premature to make recommendations regarding nutritional supplementation to avoid post-exercise impairment of the immune system.